Evaluation of gamma-ray disturbing effect on readout of charged particle tracks using fluorescent nuclear track detectors (FNTDs). (March 2019) - Hashizume, Takuya; Okazaki, Tohru; Sanami, Toshiya; Hagiwara, Masayuki; Monjushiro, Hideaki; Hayashi, Hiroaki; Kobayashi, Ikuo
Abstract: In this study, we aimed to identify the reasons for track misrecognition caused by gamma-rays in the FNTD (fluorescent nuclear track detector) system. FNTDs were irradiated with fluence-controlled 241 Am alpha-particles at 0°. The irradiated FNTDs were scanned by a commercial reader to obtain fluorescence images of uniform shape tracks and a reader-counted track density per unit area [mm −2 ]. The track density was good agreement with manually eye-counted track density. Then, the FNTDs irradiated with alpha-particles were additionally irradiated with 137 Cs gamma-rays and scanned by the reader in order to monitor transition of the reader-counted track density with gamma dose. Track counting efficiency, which is defined as the reader-counted density divided by the eye-counted density, was reliable with until 33 mSv of gamma dose with ± 30% accuracy. However, with the higher dose of gamma-rays at 95 and 242 mSv, the efficiency fluctuated over the accuracy because of track misrecognition. To clarify the reasons for the track misrecognition, fluorescence track images were compared before and after gamma irradiations. On the fluorescence images with gamma-rays, the non-uniform signal caused by secondary electrons were observed (Sykora et al., 2010a). Especially with 242 mSv of gamma dose, the non-uniform signal formed "track-like" spots. To analyze the characteristics of the non-uniform signal, fluorescence intensity ( FI ) per pixel was analyzed for track and background (BG) areas separately. The FIs at both track and BG areas showed linearity to gamma dose. In the analysis of FI distributions, the fluctuation of FIs at BG area increased with gamma doses while the fluctuation of FIs at track areas did not change significantly. As a result, the difference of FI values between track and BG areas was smaller with the higher dose of gamma-rays. This phenomenon caused the difficulty of detecting tracks under gamma-ray exposure. Highlights: The reasons of the misrecognition of tracks was studied by a quantitative analysis of fluorescent track images after gamma-ray irradiations. The bright and uniform circle tracks formed by the 0° irradiation of monoenergetic alpha-particles were analyzed. Increasing of fluctuation of fluorescence intensities at background area made it difficult to distinguish track and BG areas, which resulted in misrecognition of tracks.